2020
DOI: 10.1515/revneuro-2019-0108
|View full text |Cite
|
Sign up to set email alerts
|

A new method to predict anomaly in brain network based on graph deep learning

Abstract: Functional magnetic resonance imaging a neuroimaging technique which is used in brain disorders and dysfunction studies, has been improved in recent years by mapping the topology of the brain connections, named connectopic mapping. Based on the fact that healthy and unhealthy brain regions and functions differ slightly, studying the complex topology of the functional and structural networks in the human brain is too complicated considering the growth of evaluation measures. One of the applications of irregular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Graph analyses and corresponding algorithms have been widely used to understand the structure of functional brain networks by predicting future relationships and missing connections. 26 , 27 One group has also utilized the link prediction model to estimate brain network changes in neurodegenerative disorders including Alzheimer's and Parkinson's disease. 11 Rather than computing the node neighborhood similarity score using popular algorithms such as Common Neighbors (CN) and Preferential Attachments (PA) for direct use of graph vector features for each node, 9 the current study implemented graph embedding and extracted vector features of each node.…”
Section: Discussionmentioning
confidence: 99%
“…Graph analyses and corresponding algorithms have been widely used to understand the structure of functional brain networks by predicting future relationships and missing connections. 26 , 27 One group has also utilized the link prediction model to estimate brain network changes in neurodegenerative disorders including Alzheimer's and Parkinson's disease. 11 Rather than computing the node neighborhood similarity score using popular algorithms such as Common Neighbors (CN) and Preferential Attachments (PA) for direct use of graph vector features for each node, 9 the current study implemented graph embedding and extracted vector features of each node.…”
Section: Discussionmentioning
confidence: 99%
“…The LENGTH method is a new approach to develop a scientific network, recently proposed for the analysis of big data and disease [17][18][19]21,26]. Graph theory is a well-known method currently used for analyzing the data connection by neuroimaging or neurophysiology [26][27][28][29]. In the present work, we have used this approach to show the most frequent words found in scientific literature on pulmonary rehabilitation before and after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that at the microscopic level, the angular momentum of electromagnetic waves also has a certain mechanical effect, which will cause the particles on the propagation path to rotate. In addition, the angular momentum of electromagnetic waves can be divided into two parts, one part is called SAM and the other part is called OAM, and in order to facilitate the derivation and analysis, they are represented by S and L , respectively [ 26 , 27 ]. For a complete torus, the isophase surfaces are two helical surfaces with an angle of 180 between them, the interferogram of plane wave and spherical wave varies greatly, but the mode orbital angular momentum can still be judged from the spherical wave interferogram.…”
Section: Mechanically Reconfigurable Arrays and Neural Network Data Setsmentioning
confidence: 99%